MODELLING OF GEOGRAPHICAL REALITY: MODELLING OF GEOGRAPHICAL REALITY - Ivanov, Sabin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
From a cartographic point of view, mapping modeling can be defined as a method of creating mathematical models that are similar copies of objects of reality. They are divided into descriptive (visual) and predictive. This is the general classification of cartographic models. Descriptive models show existing objects or phenomena, as well as the links between them, presenting the results in an appropriate form that allows the user to identify them immediately. This type of model is simple and easy to create, and this reason makes it the most commonly used. The second type of cartographic model shows the predictive possibilities of the descriptive model and is called a predictive cartographic model. Predictive models require the introduction of factors and parameters that are important for the functioning of phenomena appearing in a particular territory.